Snowball Throwing in Teaching Grammar - Yanuarti Apsari (Lingual, 2018)
The aims of this study are to describe the implementation of snowball throwing in teaching grammar and to investigate the benefits of applying snowball throwing. The research was conducted at STKIP Siliwangi Bandung. This study applied qualitative research involving one class consisting of second semester students in English Department who were taking the subject of foundation of English Grammar. The data were obtained from classroom observation and students’ interview. The findings showed that there are seven stages in implementing snowball throwing in teaching grammar. The stages consist of preparing teaching material, forming group, re-explaining the material to the member of the group, formulating question, tossing the ball, answering questions and evaluating teaching and learning process. In addition, the findings also revealed that there are some benefits from applying snowball throwing in teaching grammar such as improving students’ comprehension in learning grammar, creating enjoyable learning atmosphere, increasing students’ vocabulary, developing students’ speaking skill, developing students’ cooperation skill and increasing students’ participation in the class.